2021
DOI: 10.1039/d1cy01277k
|View full text |Cite
|
Sign up to set email alerts
|

Comparison study of the effect of CeO2-based carrier materials on the total oxidation of CO, methane, and propane over RuO2

Abstract: The effect of the carrier material on the intrinsic activity of three catalytic total oxidation reactions, namely CO oxidation as well as methane and propane combustion over highly dispersed RuO2...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…At the same time, C 2 H 6 is more active than CH 4 on Pt and Pd. This difference in activation may be attributed to the fact that the first reaction step forming the alkyl group requires less energy in the case of C 2 H 6 than in the CH 4 case . The comparison presented here for the four fuels on both Pt and Pd is new to the literature.…”
Section: Discussion and Analysismentioning
confidence: 85%
See 1 more Smart Citation
“…At the same time, C 2 H 6 is more active than CH 4 on Pt and Pd. This difference in activation may be attributed to the fact that the first reaction step forming the alkyl group requires less energy in the case of C 2 H 6 than in the CH 4 case . The comparison presented here for the four fuels on both Pt and Pd is new to the literature.…”
Section: Discussion and Analysismentioning
confidence: 85%
“…This difference in activation may be attributed to the fact that the first reaction step forming the alkyl group requires less energy in the case of C 2 H 6 than in the CH 4 case. 78 The comparison presented here for the four fuels on both Pt and Pd is new to the literature. Still, we consider partially similar studies in the literature.…”
Section: ■ Discussion and Analysismentioning
confidence: 98%
“…Ruthenium is known to be one of the most active elements in the activation of C−H and C−C bonds, [21] thus making it a promising and less expensive alternative to Pt for the removal of higher hydrocarbons. In several studies the excellent activity of Ru‐based catalysts in propane combustion has been demonstrated [22–27] . For example, for the same feed gas and gas hourly space velocity, the activity of Ru/CeO 2 sample is 1.5 times higher than that that of Pt/ZSM−S catalysts at 200 °C [25,28] .…”
Section: Introductionmentioning
confidence: 99%
“…In several studies the excellent activity of Ru-based catalysts in propane combustion has been demonstrated. [22][23][24][25][26][27] For example, for the same feed gas and gas hourly space velocity, the activity of Ru/CeO 2 sample is 1.5 times higher than that that of Pt/ ZSMÀ S catalysts at 200 °C. [25,28] However, Ru-based catalysts tend to deactivate via loss of active surface area by sintering or by transformation into volatile RuO 4 at higher temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the RuO 2 –support interface is directly involved in the activation of hydrocarbon molecules, literature teaches that Ru catalysts with reducible supports are better hydrocarbon oxidizers, and Ru/CeO 2 is usually considered more reactive for hydrocarbon combustion compared to other Ru catalysts. For example, at the same feed gas and gas hourly space velocity, the propane turnover frequencies over Ru/CeO 2 were reported to be 3.8 and 1.8 times higher than those over Ru/γ-Al 2 O 3 and Ru/ZrO 2 at 210 °C, respectively . Within such a framework, the size of supported RuO 2 is of great importance because the atomic species and small clusters give rise to longer RuO 2 perimeters and added RuO 2 –CeO 2 interfacial sites, which may therefore benefit more from the support reducibility in contrast to larger supported RuO 2 particles. , A conventional strategy to obtain Ru/CeO 2 catalysts with maximized Ru dispersion is reducing the Ru loading amount to, e.g., ≤0.25 wt %. , Such loadings are, however, significantly lower than those in commercial oxidation catalysts (e.g., 1 wt % Pt/γ-Al 2 O 3 ) and may lead to limited overall catalytic performance per unit reactor volume or area in large-scale processes.…”
Section: Introductionmentioning
confidence: 99%